Preoperative Lignocaine Nebulization for Attenuation of the Pressor Response of Laryngoscopy and Tracheal Intubation in Patients Undergoing Laparoscopic Cholecystectomy Under General Anesthesia - Shakya, Shailendra; Shakya, Anuka; Paudel, Bibek (Journal of Nepalgunj Medical College, 2025)
Introduction: Laryngoscopy and intubation during laparoscopic cholecystectomy under general anesthesia can cause a pressor response, resulting in hemodynamic instability. Preoperative lignocaine nebulization provides topical anesthesia by inhibiting sodium channels and may offer better mucosal coverage than intravenous administration. Aims: To assess the effect of lignocaine nebulization on pressor response, hemodynamic stability, and related complications. Methods: This double-blinded comparative study was conducted from August to December 2024, involving 100 patients undergoing elective surgery under general anesthesia with physical status score I or II (American Society of Anesthesiologists). Patients were randomized into two groups for nebulization: Group A (n=50) received 2% lignocaine (3 mg/kg, volume adjusted with saline), while Group B (n=50) received an equivalent volume of 0.9% normal saline. Parameters analyzed included age, gender, weight, ASA physical status, SpO2, heart rate and mean arterial pressure. Statistical analysis was performed using Student’s t-test and Chi-square test; p<0.05 was considered significant. Results: Both groups were comparable in terms of age, gender, physical status and mean duration of surgery. In group A, the baseline Heart Rate was 89.34 ± 12.12 per minute while in group B 88.26 ± 10.98 per minute. Two minutes after intubation, it increased and started declining from the 4th minute in both the groups. However, there were significant statistical difference between two groups at 2 and 4 minutes respectively (p = 0.001 and 0.038). Mean arterial pressure (MAP) also rose in both groups at 2 minutes, but the increase was significantly greater in group B (p=0.001). This difference remained significant at 4 minutes (p=0.001), with no significant variation observed from the 6th minute onward. Conclusion: Preoperative lignocaine nebulization effectively bluntsthe pressor response to laryngoscopy and intubation, enhancing hemodynamic stability and perioperative safety.